Impact of Nutrition Education to Rural Women for Prevention of Iron Deficiency Anemia through Dietary Approach (Indian Journal of Extension Education, 2016)
Sixty adult women in the age group of 25-35 years belonging to farm families were selected. The basic meal of dal and chapati supplemented with individual key foods such as salad, orange, lemonade, chicken, milk, curd, egg and tea were analyzed for total iron, dialyzable iron and in vitro iron bioavailability. The knowledge generated through experiment was transferred to the surveyed women through a nutrition education. Inclusion of 200 g of chicken and 250 ml of lemonade to the basic meal enhanced iron absorption by 25.74 per cent and 12.16 per cent , respectively. The in vitro bioavailability of iron was reduced by 3.8 and 1.5 per cent, when basic meal was fortified either by milk or curd, respectively. The major inhibitors of iron bioavailability were egg and tea, the percent reduction caused by egg being 50.2 per cent while by tea it was 44.6 per cent. The nutrition education intervention through a developed visual aid proved effective in improving the knowledge of rural women regarding anemia and its prevention through a dietary approach as the mean gain in knowledge was 67.8 per cent. Hence, nutrition education to women folk can prove effective in preventing iron deficiency anemia.